Management of serpentine leafminer (Liriomyza trifolii) (Diptera: Agromyzidae) on tomato (Lycopersicon esculentum) with a new insecticide cyantraniliprole - MISRA, H P (The Indian Journal of Agricultural Sciences, 2013)
A field experiment was conducted at the Central Research Station farm of Orissa University of Agriculture &Technology, Bhubaneswar, Odisha, India during winter seasons of 2009-10 and 2010-11 to evaluate the bio-efficacy of a new anthranilic diamide, cyantraniliprole (Cyazypyr) (HGW 86) 10% OD for its efficacy in controlling the serpentineleafminer [Liriomyza trifolii (Burgess)] (Diptera: Agromyzidae) infesting tomato (Lycopersicon esculentum Mill) crop and its safety to the coccinellid predators. Superiority of cyantraniliprole (HGW86) 10% OD @ 90 and 105 g a.i./ha wassignificantly envisaged with record of lowest number of serpentine leafminer (SLM) adults/5 plants (0.66-0.74 in 2009– 10 and 0.77-0.85 in 2010–11) at 7 days after spraying (DAS) in comparison to other treatments registering a mean of 80.65-82.61% reduction in SLM adult population over control. The results further revealed significantly lowest number of live mines/20 leaves (2.33-2.58 in winter, 2009–10 and 2.40-2.67 in winter, 2010–11) by SLM in treatmentscyantraniliprole (HGW 86) 10% OD @ 90 and 105 g a.i./ha with a mean reduction of 83.95-85.54% live mines overcontrol compared to other treatments during both the seasons of experimentation. Significantly lowest number of SLM pupae was observed in the plots receiving treatments cyantraniliprole (HGW 86) 10% OD @ 90 and 105 g a.i./ha both during 2009–10 (1.15-1.33) and 2010–11 (1.10-1.25), when compared to untreated control, with a mean reduction of83.67-85.76% SLM pupal population over control. The predatory coccinellid population did not differ significantly from that of control during post application period indicating safety of cyantraniliprole and spinosad at tested doses to thepredators except for endosulfan treatment. The mean marketable tomato fruit yield was recorded significantly highest (16.26-16.65 tonnes/ha) in treatments cyantraniliprole (HGW 86) 10% OD @ 90 and 105 g a.i./ha with an increase of 48.90-52.49% over untreated control.